112 B-type Natriuretic Peptide is Associated with Future Rise in Lv Mass in Optimally Treated Primary Prevention Population. (31st May 2014) - Nadir, Adnan; Gandy, Steve; Struthers, Allan
Abstract : Background: Several studies including both the Framingham study and the Olmstead county population study show that BNP predict prognosis over and above a wide range of echo abnormalities at baseline. The reason for this is unknown but one hypothesis is that an elevated BNP is an early sensitive indicator of who will develop future structural abnormalities such as LV hypertrophy. Methods: We identified optimally treated primary prevention patients with no cardiac abnormality at baseline.In particular, they had no myocardial ischaemia or LV hypertrophy or LV dysfunction or left atrial enlargement.The patients underwent cardiac magnetic resonance (CMR) imaging at baseline and 3 years later on a 3T scanner. Results: 50 patients (Mean age 64 years, 59% male) with a diverse range of plasma BNP levels were studied. The average LV mass at baseline was 105 ± 24 g and 55 ± 9 g/m 2 when indexed to BSA. At follow up, LV mass increased (+4·7 ± 3·5 g) in 24 patients and decreased (-4·9 ± 2·8g) in 26 patients (p < 0·01).Blood pressure by 24 h monitoring was virtually identical between those whose LV mass increased (SBP 122 ± 14 mmHg) and those whose LV mass decreased (SBP 121 ± 11 mmHg p = 0·77).Plasma BNP was nearly three times higher in those whose LV mass increased versus those in whom LV mass decreased (21 ± 9·6 pg/ml vs. 7·9 ± 3·9 pg/ml p < 0·01). Conclusion: In optimally treated primary prevention patients, plasma BNP levels are able to distinguish between those whose LV mass will increase over the next 3 years versus those whose LV mass will decrease over the next 3 years.This may explain why high BNP individuals are at increased risk even if no cardiac abnormality can be detected initially.